Cooperation in the greater Caribbean : the role of the Association of Caribbean States - Girvan, Norman (Ian Randle KingstonJM, 2006)
Discusses the geo-political and geo-economic context in which the ACS emerged and outlines a vision of the greater Caribbean as a zone of cooperation. Analyses the achievements and shortcomings of the Association as it approached its 10th anniversary. Discusses the main areas of ACS cooperation as well as key economic and political developments affecting the greater Caribbean during the period.